Author Correction: The social and cultural roots of whale and dolphin brains. Issue 1 (January 2018) - Fox, Kieran; Muthukrishna, Michael; Shultz, Susanne
In Table 1 of the Supplementary Information, the data presented in the column 'Corrected social repertoire' were incorrect. This error does not affect the analyses, statistics or conclusions of the study, which employed the correct values. The data have now been corrected in the Supplementary file.